WORK PROCRASTINATION: A SYSTEMATIC LITERATURE REVIEW OF THE FACTORS CONTRIBUTING TO TASK PROCRASTINATION IN THE PROFESSIONAL ENVIRONMENT - Wisnu Budi Prasetyo; Hendy Tannady; Rina Anindita; Rojuaniah Rojuaniah (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Work procrastination is a common phenomenon in various work environments and can have a negative impact on employee productivity, performance, and welfare. This study aims to systematically review the existing literature on the factors that contribute to task procrastination in the professional environment. Through a literature search in various academic databases, this study identified and analyzed the psychological, contextual, and individual factors that influence work procrastination. The results of the review show that factors such as anxiety, perfectionism, self-uncertainty, and low self-regulation are the main causes of procrastination of tasks. In addition, contextualities such as excessive workload, role ambiguity, and unsupportive work environments were also found to have significant contributions. The study also discusses various strategies for dealing with work procrastination, including psychological interventions and time management. These findings provide important insights for organizations and individuals in formulating more effective approaches to minimize task delays in the work environment. Keywords: work procrastination, task procrastination, psychological factors, professional environment, time management, psychological intervention, self-regulation.